Evaluating Parallel Simulated Evolution Strategies for VLSI Cell Placement - Sait, Sadiq M. (2007)
Simulated Evolution (SimE) is an evolutionary metaheuristic that has produced results comparable to well established stochastic heuristics such as SA, TS and GA, with shorter runtimes. However, for optimization problems with a very large set of elements, such as in VLSI cell placement and routing, runtimes can still be very large and parallelization is an attractive option for reducing runtimes. Compared to other metaheuristics, parallelization of SimE has not been extensively explored. This paper presents a comprehensive set of parallelization approaches for SimE when applied to multiobjective VLSI cell placement problem. Each of these approaches are evaluated with respect to SimE characteristics and the constraints imposed by the problem instance. Conclusions drawn can be extended to parallelization of SimE when applied to other optimization problems.